Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevb.85.224507
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of superconducting nanowires shunted with an external resistor

Abstract: We present the first study of superconducting nanowires shunted with an external resistor, geared towards understanding and controlling coherence and dissipation in nanowires. The dynamics is probed by measuring the evolution of the V -I characteristics and the distributions of switching and retrapping currents upon varying the shunt resistor and temperature. Theoretical analysis of the experiments indicates that as the value of the shunt resistance is decreased, the dynamics turns more coherent presumably due… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 67 publications
6
52
1
Order By: Relevance
“…For this purpose, we need to know approximate values of the effective shunt capacitance, the shunt impedance, and the critical current of the nanowires. According to previous studies [18,38], the critical current of our nanowires is of the order of 10 μA. The effective shunt impedance is set by the waveguide impedance of the resonator, which is R n ∼ 50 Ω.…”
Section: Fig 6 Rates Of Sps (Blue Squares) and Pps (Red Ovals) Asmentioning
confidence: 95%
“…For this purpose, we need to know approximate values of the effective shunt capacitance, the shunt impedance, and the critical current of the nanowires. According to previous studies [18,38], the critical current of our nanowires is of the order of 10 μA. The effective shunt impedance is set by the waveguide impedance of the resonator, which is R n ∼ 50 Ω.…”
Section: Fig 6 Rates Of Sps (Blue Squares) and Pps (Red Ovals) Asmentioning
confidence: 95%
“…The assumed immediate sharing of the bias current between WL and R s implies a small inductive currentswitching time as compared to the thermal equilibration time. The minimum shunt resistor value, R sc , from our simple model can also describe the behavior of shunted nano-wire devices studied by Brenner et al [11].In this Letter, we compare the current-voltage characteristics of carefully designed WL devices with (and without) a shunt resistor kept in close vicinity of the WL, thus making the inductive current-switching time smaller than the thermal equilibration time. We observe an increase in the re-trapping current and a widening of the hysteresis-free temperature range thanks to the shunt, which we discuss using the above model.…”
mentioning
confidence: 77%
“…3,17,18 Shunting of the channel by a resistor narrows this hysteresis and, for small enough resistance, the hysteresis disappears. 18 It was suggested that shunting is able to influence the phase-slip events and hence can be used for control of dissipation and coherence in nanowires. 18 However, the dynamical mechanisms involved in the formation of the hysteresis are still not clear, and the ways that shunting drives the phase-slip events are not fully apprehended.…”
Section: Introductionmentioning
confidence: 99%
“…18 It was suggested that shunting is able to influence the phase-slip events and hence can be used for control of dissipation and coherence in nanowires. 18 However, the dynamical mechanisms involved in the formation of the hysteresis are still not clear, and the ways that shunting drives the phase-slip events are not fully apprehended. In this paper we study the dynamics of the resistive state in a narrow superconducting channel shunted by an external resistor and explore the bifurcation mechanisms involved in the hysteresis of CVCs and also responsible for the formation and evolution of PSCs.…”
Section: Introductionmentioning
confidence: 99%